Decomposition of Organic Matter in Caves - Ravn, Nynne Rand; Michelsen, Anders; Reboleira, Ana Sofia P. S. (Frontiers in Ecology and Evolution, 2020)
Decomposition of organic matter is a process, which includes mostly physical breakdown and biochemical transformation of complex organic molecules into simpler organic and inorganic molecules. The decomposition of organic matter is an important contributor to ecosystem respiration, which together with photosynthesis controls the net carbon emission from ecosystems. Subterranean ecosystems extend all over the subsurface of our planet. These lack light and consequently photosynthetic activity, and understanding the drivers that control the dynamics of the decomposition processes in the deep subterranean spaces is important. This is because they might differ from surface due to factors as low species diversity and abundance, low microbial biomass, nutrient poor conditions, less pronounced variation of temperature, and higher humidity inside cave. Here, we review the existing studies of organic matter decomposition in caves. Decomposition rates are known from only nine caves representing four biogeographic regions, including Europe, North and South America. Most of the studies were performed in the aquatic compartment of caves. The decay of nine different organic substrates were used and the incubation time varied from 36 to 439 days. From a cave located in Australia the mass loss of leaf material from three plant species were investigated after 90 days incubation in the terrestrial compartment of the cave. Based on these observations, litter quality seems to be an important driver of decomposition in caves and invertebrates have a stimulating effect on the decomposition within individual cave zones. The degree of connection to the surface do also influence decomposition rate inside the cave. The lack of standard data among the studies is currently the major impediment to evaluate how differently the process proceeds in the underground compared to the surface, and to clearly identify the main drivers of decomposition in caves across biomes. Improving our understanding of organic matter decomposition dynamics in caves across biomes will require standardization of protocols and evaluation of the process over time, and a better comprehension on how decomposition changes over latitudinal, altitudinal and depth gradients.